Twenty-First Year of Global Research on Flyash: A Review - Kumar, Rajesh; Bhardwaj, Atul Kumar; Chandra, K.K.; Shukla, Arun Kumar; Singh, Anish Kumar (Indian Forester, 2025)
Fly ash is a fine particle by-product of pulverized coal combustion derived mostly from coal-fired power plants. Due to the increasing population in the world, electrical energy consumption has reached an all-time high. To cope with the power demands, the power industries increase their production, producing an enormous quantity of fly ash and creating environmental problems. Worldwide, coal-based power plants dominate energy production rather than other energy sources such as wind and solar energy. Fly ashes are utilized for several purposes, such as cement, bricks, building materials, etc. However, its restoration potential is still limited. In the present review, twenty-first year of published research literature related to fly ash have been summarized based on different parameters. In addition, the article also focuses on the Physico-chemical compositions and utility of fly ash across globe that influences its reuse options. The paper also gives an overview of the global scenario of fly ash generation and trends of fly ash research in the past twenty years.